Analysis of bulk oil in Tulungagung district on physical and chemical properties - Taufik Salis Syaifudin; Rizqi Asri Fauzi Nugraha; Indra Lasmana Tarigan (Medical Laboratory Analysis and Sciences Journal, 2019)
This study aims to analyze the quality of Bulk frying oil in the Tulungagung district. Four samples were a test using physical parameters, organoleptic, density, and viscosity, while the chemical parameters were a test or the value of free fatty acids, acid numbers, and peroxide numbers. Comparison of the results of the analysis with SNI (Indonesian Standard Oil Quality), the four samples have poor chemical properties quality, it could be known by the acid number of samples 0.56, 0.78, 0.78, 1.65 (%) and Free fatty acids number 2.86, 9.98, 4.23, 6.7 (%) are higher than SNI 0.3 and 0.6 (%), even sample D has a poor peroxide number. So that overall, it is shown that the quality of Bulk oil from the samples used is not good enough.